Pertumbuhan Tunas Tacca leontopetaloides L. Hasil Mikropropagasi Setelah Pemberian Radiasi Sinar Gamma Co60 dan Hormon Tumbuh yang Berbeda - Darnia Astari Parastiti; Endang Kusdiyantini; Endah Dwi Hastuti; Betalini Hapsari; Tri Muji Ermayanti (Jurnal Akademika Biologi, 2015)
Taca  (Tacca  leontopetaloides  L.)  is  one  of  the  plant  family Dioscoreaceae  that  contain compounds   glikosida   flavonoid   called   taccalin   and   taccalonoides   who   potential   as antioxidants. Taka (Tacca  leontopetaloides L.) specifically has not been cultivated, grown only a limited area around the beach, it is necessary to plant vegetative propagation system faster with more results in tissue culture systems. This study aims to determine the growth and the antioxidant potential shoots Tacca leontopetaloides L. mikropropagasi results after administration  of  Co60  Gamma  ray  radiation  and  different  growth  hormones.  Research method  uses  completely  randomized  factorial  design  (RAL)  with  4  treatment  doses  of Gamma radiation Co60 is 0 Gy, 5 Gy, 20 Gy, and 30 Gy and 3 treatment of growth hormone that MSo, MSo + 0,5 BAP and MSo + 0,5 Kinetin with 3 replicates. Shoots taka from results mikropropagasi grown in  vitro and has been irradiated with Co60 Gamma rays. Parameters tested were growth of shoots, amount of leaves, till, roots and wet weight taka. The results showed  that  Gamma radiation  Co60  and  plant  regulator  cytokinin  effect  on  shoots  taka, amount of tillers, leaf, root and wet weight taka. Keywords: Taka (Tacca leontopetaloides L.), Mikropropagation, Growth Hormone.